Uncomplicated obesity is associated with abnormal aortic function assessed by cardiovascular magnetic resonance. - Robinson, MR; Scheuermann-Freestone, M; Leeson, P; Channon, K; Clarke, K; Neubauer, S; Wiesmann, F (2008)
AIMS: Obese subjects with insulin resistance and hypertension have abnormal aortic elastic function, which may predispose them to the development of left ventricular dysfunction. We hypothesised that obesity, uncomplicated by other cardiovascular risk factors, is independently associated with aortic function. METHODS AND RESULTS: We used magnetic resonance imaging to measure aortic compliance, distensibility and stiffness index in 27 obese subjects (BMI 33 kg/m2) without insulin resistance and with normal cholesterol and blood pressure, and 12 controls (BMI 23 kg/m2). Obesity was associated with reduced aortic compliance (0.9 +/- 0.1 vs. 1.5 +/- 0.2 mm2/mmHg in controls, p < 0.02) and distensibility (3.3 +/- 0.01 vs. 5.6 +/- 0.01 mmHg-1 x 10-3, p < 0.02), as well as higher stiffness index (3.4 +/- 0.3 vs. 2.1 +/- 0.1, p < 0.02). Body mass index and fat mass were negatively correlated with aortic function. Leptin was higher in obesity (8.9 +/- 0.6 vs. 4.7 +/- 0.6 ng/ml, p < 0.001) and also correlated with aortic measures. In multiple regression models, fat mass, leptin and body mass index were independent predictors of aortic function. CONCLUSION: Aortic elastic function is abnormal in obese subjects without other cardiovascular risk factors. These findings highlight the independent importance of obesity in the development of cardiovascular disease.